Stateless Transnational Migrant Children in South Africa: Implications and Opportunities for Social Work Intervention - Warria, Ajwang’ (African Human Mobility Review, 2021)
Migrant children who are vulnerable to statelessness are a growing at-risk population worldwide, and in South Africa. Migrant children often travel unaccompanied or become separated from their families during the journey, thus increasing their vulnerability. These children are often denied their rights in countries of transit and resettlement and might even be detained due to lack of documentation. They are subject to high levels of violence and status-exclusion within the migratory process. This paper considers statelessness in migrant children in South Africa, and undertakes a review of the literature to understand this phenomenon. The results show that a considerable number of migrant children in South Africa are at risk of statelessness. While all children may have roots that can be traced, situations and technicalities arise within the migration and registration framework that result either in children becoming stateless or at risk of becoming such. These children’s childhoods fall through the gaps as they lack a sense of belonging. They also have limited rights and none of the protection that goes with being recognized as nationals. Social workers are able to play a significant role in assessing and determining if migrant children are either stateless or at risk of becoming stateless and offer appropriate intervention to help them realize their rights, potential and contributions.